Design, development, and optimization of sumatriptan loaded ethosomal intra-nasal nanogel for brain targeting - Nerella, Nagadivya; Vasudha, Bakshi (Creative Pharma Assent, 2024)
Background: Sumatriptan is one of the most essential drugs for treating migraine. However, dosage-related side effects are still a worry despite its 14 % oral bioavailability and recurrence of migraine-associated diseases. Methodology: The fundamental focus of the study is to develop the sumatriptan intra-nasal nano-ethsomal gel by film hydration technique with the aid of QbD principles that govern the varied compositions and blends of polymers like HPMC K100M and Phospolipon 90G to develop a sustained release dosage form. Results and discussion: The preliminary FT-IR and DSC studies revealed no interactions between the drug and their physical mixtures. The present study considered three observable responses: vesicle size, zeta potential, and percent drug release after 24 h, taken into consideration during the optimization of the ethosomal formulations utilizing 32 central composite designs (CCD). The vesicle size (122.23 nm), zeta potential (-40.2 mV), and drug release percentage (92.61 %) for all formulations were seen in the F12 batch after 24h. The p-XRD and SEM studies indicated that the nano-ethosomal gel was stable. The stability studies indicated the preparation of a more stable formulation for the parameters under the study protocol. Conclusion: Using a novel intra-nasal brain targeting approach by adapting the film hydration technique, the current issues might be addressed, and the drug's duration of residence at the absorption site uptake substantially increase. To efficiently modify the drug's residence through the intra-nasal route, this work focuses on developing a nano-ethosomal gel loaded with sumatriptan.